Effect of SALAD Technique on CPR Quality During Intubation in Contaminated Airways: A Randomized Controlled Manikin Simulation Study - Li-Wei Lin; James DuCanto; Yung-Cheng Su; Chee-Fah Chong; Chi-Chieh Huang; Shih-Wen Hung (Emergency Medicine International, 2025)
Conclusions: The SALAD technique achieved higher chest compression rates and provided better glottic visualization compared to intermittent suction during intubation in contaminated airways.